SYNTHESIS OF THERMOREACTIVE OLIGOMERS ON THE BASIS OF POLYCYCLIC BISPHENOLS - Givi Papava; Marina Gurgenishvili; Ia Chitrekashvili; Zurab Chubinishvili; Zurab Tabukashvili (World Science, 2018)
Novolac on the base of norbornane type bisphenol was obtained. Some cinetic regularities of reaction of interaction of norbornane type bisphenol and formaldehyde were studied. It was proved that the reaction proceeded according to the second order. IR-spectroscopy was used to study the process of thermal hardening of novolac at isothermal terms on the air.